Control of Candida albicans Murine Vaginitis by Topical Administration of Polycarbophil-Econazole Complex - Ghelardi, E. (American Society for Microbiology, 1998)
The complexation of econazole with the mucoadhesive polycarbophil was found to significantly improve the therapeutic benefit of the drug in the topical treatment of experimental vaginal candidiasis in mice, while no difference in the antimycotic activity exerted by econazole and polycarbophil-econazole could be detected in vitro.